Determinants of Health-Related Quality of Life After ICU: Importance of Patient Demographics, Previous Comorbidity, and Severity of Illness. Issue 4 (April 2018) - Griffith, David M.; Salisbury, Lisa G.; Lee, Robert J.; Lone, Nazir; Merriweather, Judith L.; Walsh, Timothy S.
Abstract : Objectives: ICU survivors frequently report reduced health-related quality of life, but the relative importance of preillness versus acute illness factors in survivor populations is not well understood. We aimed to explore health-related quality of life trajectories over 12 months following ICU discharge, patterns of improvement, or deterioration over this period, and the relative importance of demographics (age, gender, social deprivation), preexisting health (Functional Comorbidity Index), and acute illness severity (Acute Physiology and Chronic Health Evaluation II score, ventilation days) as determinants of health-related quality of life and relevant patient-reported symptoms during the year following ICU discharge. Design: Nested cohort study within a previously published randomized controlled trial. Setting: Two ICUs in Edinburgh, Scotland. Patients: Adult ICU survivors ( n = 240) who required more than 48 hours of mechanical ventilation. Interventions: None. Measurements and Main Results: We prospectively collected data for age, gender, social deprivation (Scottish index of multiple deprivation), preexisting comorbidity (Functional Comorbidity Index), Acute Physiology and Chronic Health Evaluation II score, and days of mechanical ventilation. Health-related quality of life (Medical Outcomes Study Short Form version 2 Physical Component Score and Mental Component Score) and patient-reported symptoms (appetite, fatigue, pain, joint stiffness, and breathlessness) were measured at 3, 6, and 12 months. Mean Physical Component Score and Mental Component Score were reduced at all time points with minimal change between 3 and 12 months. In multivariable analysis, increasing pre-ICU comorbidity count was strongly associated with lower health-related quality of life (Physical Component Score β = –1.56 [–2.44 to –0.68]; p = 0.001; Mental Component Score β = –1.45 [–2.37 to –0.53]; p = 0.002) and more severe self-reported symptoms. In contrast, Acute Physiology and Chronic Health Evaluation II score and mechanical ventilation days were not associated with health-related quality of life. Older age (β = 0.33 [0.19–0.47]; p < 0.001) and lower social deprivation (β = 1.38 [0.03–2.74]; p = 0.045) were associated with better Mental Component Score health-related quality of life. Conclusions: Preexisting comorbidity counts, but not severity of ICU illness, are strongly associated with health-related quality of life and physical symptoms in the year following critical illness. Abstract : Supplemental Digital Content is available in the text.